Orthodontics Surgical Assistance (Piezosurgery®): Experimental Evidence According to Clinical Results - Dario Bertossi; Dario Donadello; Giamaica Conti; Luca Calogero Carletta; Andrea Sbarbati; Claudia Corega; Alessandra Luise Marie Magistretti; Alessandra Lucchese; Giovanni Salzano; Giulia Ricciardi; Pier Francesco Nocini (Applied Sciences, 2022)
Orthodontic tooth movement (OTM) is based on intermitted or continuous forces applied to teeth, changing the mechanical loading of the system and arousing a cellular response that leads to bone adaptation. The traditional orthodontic movement causes a remodeling of the alveolar bone and changes in the periodontal structures that lead to tooth movement. The use of a piezoelectric instrument in orthodontic surgery has already shown great advantages. The purpose of this study is to rank the behavior of inflammatory mediators in accelerating orthodontic tooth movement. Ten patients with malocclusion underwent orthodontic surgical treatment, which included a first stage of surgically guided orthodontic movement (monocortical tooth dislocation and ligament distraction, MTDLD) to accelerate orthodontic movements. In all cases, corticotomy was performed by Piezosurgery. Bone and dental biopsy was executed to evaluate changes in the cytokines IL-1beta, TNF-alpha and IL-2 in different time intervals (1, 2, 7, 14 and 28 days). The molecular mediators are IL-1 beta, TNF-alpha and IL-2. Immediately after the surgical procedure there was a mild expression of the three molecular markers, while the assertion of IL-1 beta and TNF-alpha reached the maximum value after 24 h and 48 h, indicating a strong activation of the treated tissues. The Piezosurgery® surgical technique induces an evident stress in short times, within 24–48 h from the treatment, but it decreases significantly during the follow-up.